CD34+CD146+ adipose‐derived stromal cells enhance engraftment of transplanted fat. (15th June 2020) - Borrelli, Mimi R.; Patel, Ronak A.; Blackshear, Charles; Vistnes, Stephanie; Diaz Deleon, Nestor M.; Adem, Sandeep; Shen, Abra H.; Sokol, Jan; Momeni, Arash; Nguyen, Dung; Longaker, Michael T.; Wan, Derrick C.
Abstract: Fat grafting is a surgical technique able to reconstruct and regenerate soft tissue. The adipose‐derived stromal cells (ASCs) within the stromal vascular fraction are believed to drive these beneficial effects. ASCs are increasingly recognized to be a heterogeneous group, comprised of multiple stem and progenitor subpopulations with distinct functions. We hypothesized the existence of an ASC subpopulation with enhanced angiogenic potential. Human ASCs that were CD34+CD146+, CD34+CD146−, or CD34+ unfractionated (UF) were isolated by flow cytometry for comparison of expression of proangiogenic factors and endothelial tube‐forming potential. Next, lipoaspirate was enriched with either CD34+CD146+, CD34+CD146−, CD34+ UF ASCs, or was not enriched, and grafted beneath the scalp skin of immunodeficient CD‐1 Nude mice (10 000 cells/200 μL/graft). Fat retention was monitored radiographically more than 8 weeks and fat grafts were harvested for histological assessment of quality and vascularization. The CD34+CD146+ subpopulation comprised 30% of ASCs, and exhibited increased expression of vascular endothelial growth factor and angiopoietin‐1 compared to CD34+CD146− and CD34+ UF ASCs, and increased expression of fibroblast growth factor‐2 compared to CD34+CD146− ASCs. The CD34+CD146+ subpopulation exhibited enhanced induction of tube‐formation compared to CD34+CD146− ASCs. Upon transplantation, fat enriched CD34+CD146+ ASCs underwent less resorption and had improved histologic quality and vascularization. We have identified a subpopulation of CD34+ ASCs with enhanced angiogenic effects in vitro and in vivo, likely mediated by increased expression of potent proangiogenic factors. These findings suggest that enriching lipoaspirate with CD34+CD146+ ASCs may enhance fat graft vascularization and retention in the clinical setting. Abstract : CD146+ adipose‐derived stromal cells express increased levels of proangiogenic factors VEGF, ANGPT1, FGF and enhance tube‐formation by vascular endothelial cells. Fat grafts enriched this subpopulation also undergo the least resorption and possess improved histologic quality and vascularization. Enriching lipoaspirate with CD146+ ASCs may enhance fat graft retention in the clinical setting.